Physiological and performance characteristics of adolescent club volleyball players - Melrose, D. R.; Spaniol, F. J.; Bohling, M. E.; Bonnete, R. A. (The Journal of Strength and Conditioning Research, 2007)
The objective of this investigation was to examine the physical and performance characteristics of adolescent club volleyball players. Twenty-nine adolescent girls, aged 12 to 17 years (14.31 +/- 1.37) were participants in this investigation. All athletes were members of a competitive volleyball club. The following group values were obtained: height (HT) = 1.69 +/- 0.08 m, weight (WT) = 59.6 +/- 8.2 kg, body fat percentage (BF%) = 20.9 +/- 4.5, lean body mass (LBM) = 46.7 +/- 4.9 kg, modified sitand-reach (MSR) = 38.7 +/- 7.1 cm, shoulder rotation (SR) = 29.4 +/- 5.6 cm, isometric hand grip (IHG) = 34.5 +/- 5.5 kg, isometric leg strength (ILS) = 77.4 +/- 18.1 kg, vertical jump (VJ) = 35.5 +/- 6.2 cm, standing broad jump (SBJ) = 178.8 +/- 20.3 cm, 1-minute situps (SU) = 47.0 +/- 6.7, T-test (TT) = 11.2 +/- 0.8 seconds., shuttle test (SHT) = 9.7 +/- 0.4 seconds, stork stand (SS) = 8.1 +/- 4.1 seconds, serving velocity (SVV) = 16.1 +/- 4.5 m/s, and spiking velocity (SKV) = 16.9 +/- 2.4 m/s. For purposes of analysis, players were divided into 2 age groups: 12 to 14 years (group A) and 15 to 17 years (group B). Significant differences (p < 0.05) were found between age groups for the following values: HT, WT, LBM, IHG, ILS, SBJ, and SVV. Values for group B were greater for each variable. Significant correlations include age and IHG (r = 0.75), age and ILS (r = 0.51), age and SBJ (r = 0.67), age and SVV (r = 0.71), LBM and IHG (r = 0.90), LBM and ILS (r = 0.62), LBM and SVV (r = 0.58), SVV and IHG (r= 0.60), and SKV and SS (r = 0.60). Our results suggest that age, experience, LBM, shoulder, hip, and thigh girths, strength, and balance are key physical performance characteristics of adolescent girls who play volleyball. Potentially, this type of information will allow coaches and athletes to identify physical and performance data specific to age groups for purposes of evaluation and player development.